Antihypertensive and Renal Mechanisms of SGLT2 (Sodium-Glucose Linked Transporter 2) Inhibitors. Issue 4 (April 2020) - Wilcox, Christopher S.
Abstract : Empaglifolzin, canagliflozin, and dapagliflozin are SGLT2 (sodium-glucose linked transporter type 2) inhibitors for treatment of type 2 diabetes mellitus that also reduce blood pressure, mortality, and cardiovascular disease and slow the loss of glomerular filtration rate. SGLT2 inhibitors inhibit the coupled reabsorption of sodium and glucose from the proximal tubules, thereby increasing renal glucose and sodium excretion, but they have more widespread renal effects, including inhibition of the sodium:proton exchanger. They increase the delivery of sodium to the loop of Henle and can thereby activate the tubuloglomerular feedback response to correct glomerular hyperfiltration. There are multiple potential mechanisms whereby these drugs lower blood pressure and preserve kidney function that are the focus of this review.